Comparison Between the Two Methods of Maximum Likelihood and Partial Estimators of The Topp - Leone Distribution Function and Reliability Using Simulation - Mohammed Ibrahim Zamel (Universitas Negeri Malang, 2026)
The study looked at how to estimate the reliability function for the Topp and Leone distribution with a shape parameter by comparing two methods: the maximum likelihood method and the method of partial estimators. The software function was used to calculate the distribution parameter estimates. An experimental study was also conducted using simulation for comparison purposes and to practically demonstrate the efficiency of these methods. This was done by relying on specific observations for different samples, comparing them based on several metrics represented by the mean squared error. It was found that as the sample size increased, the maximum likelihood estimator became the best.